Identificação e filogenia molecular de Brycon (Characiformes, Characidae : Bryconinae) cisandinos - Arruda, Pábila Stephanie de Souza (2022)
Species are considered the unit of biological studies, identified in morphological studies and used data; However, there are some taxa that are logically morphologically enigmatic and with little taxonomic information, which makes this form of identification difficult. In these cases, the delimitation of the use of DNA sequences is a proposal to estimate the limits of species that has been widely used to generate hypotheses. New species are discovered and described each year, estimates indicate that the diversity exceeds 9,000 species; about a third has not yet been described. In this study, we evaluated the genus Brycon, which represents an important group of fish in the Neotropical region. They are medium to large fish, migratory, omnivorous, with outstanding ecological and economic importance. Studies using morphological and molecular data within the genus have revealed sampling gaps, many unknown or even misidentified species and many taxonomic problems that need clarification. The objective of this study was to identify the Molecular Operational Taxonomic Units (MOTUs) of the genus Brycon using the COI mitochondrial gene, from different watersheds in South America and to evaluate the phylogenetic relationships between the species of the genus, using mitochondrial markers (COI, Cyt B and 16S) and nuclear (S7). In addition to describing a new record of the species Brycon amazonicus for the Paraguay River Basin, Brazil. The results obtained in the present study identified 29 delimited Brycon lineages, of which 18 are valid species and the other 11 correspond to potential species to be described, which indicates a greater molecular diversity than what was estimated based on the described species. Brycon is a polyphyletic genus, confirmed in this study. The results recovered Brycon together with Chilobrycon and Henochilus. Studies on fish diversity involving molecular analysis have shown a high species richness, underestimating the real existing diversity. Our results represent an important step towards understanding the relationships and diversity of species in the genus Brycon.